2008
DOI: 10.1002/qua.21812
|View full text |Cite
|
Sign up to set email alerts
|

Nonadditivity of methyl group in single‐electron hydrogen bond of methyl radical‐water complex

Abstract: ABSTRACT:The nonadditivity of methyl group in the single-electron hydrogen bond of the methyl radical-water complex has been studied with quantum chemical calculations at the UMP2/6-311ϩϩG(2df,2p) level. The bond lengths and interaction energies have been calculated in the four complexes: CH 3 OH 2 O, CH 3 CH 2 OH 2 O, (CH 3 ) 2 CHOH 2 O, and (CH 3 ) 3 COH 2 O. With regard to the radicals, tert-butyl radical forms the strongest hydrogen bond, followed by iso-propyl radical and then ethyl radical; methyl radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Hence, the hydrogen atoms in the methyl radical are substituted stepwise by 1-3 methyl groups, respectively. 11 As is expected, with the increase of the number of methyl groups in the methyl radical, the interaction energy becomes more negative. 7 with the interaction energies listed in Table 5.…”
Section: Substituent Effectmentioning
confidence: 62%
See 1 more Smart Citation
“…Hence, the hydrogen atoms in the methyl radical are substituted stepwise by 1-3 methyl groups, respectively. 11 As is expected, with the increase of the number of methyl groups in the methyl radical, the interaction energy becomes more negative. 7 with the interaction energies listed in Table 5.…”
Section: Substituent Effectmentioning
confidence: 62%
“…The single-electron halogen bond shows a positive nonadditivity of the methyl group, 22 which is different from the negative one in the hydrogen-bonded complex CH 3 Á Á ÁH 2 O. 11 An ab initio study was performed to compare the singleelectron hydrogen, lithium, and halogen bonds by applying HBe, H 2 B, and H 3 C radicals as the electron donors, and the results showed that the interactions become stronger in order of H 3 C o HBe o H 2 B. 23 Single-electron halogen and pnicogen bonds belong to the s-hole interaction, which is an attractive interaction between the Lewis bases and the s-hole, a region of positive electrostatic potential on the outer side of the halogen and pnicogen atoms.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, the interaction energy is −8.7 kcal/mol in FCl‐CNH, but becomes −17.2 kcal/mol in FCl‐CNH‐CNLi, doubled by the combination of cooperativity between halogen and hydrogen bonds and Li substitution . Due to its extensive presence in biology and chemistry, attention has been given to the effect of the methyl group on the strength of non‐covalent interactions . For most hydrogen bonds, the methyl group on the electron donor is electron‐donating and that on the proton donor is electron‐withdrawing, both enhancing the strength of hydrogen bonding .…”
Section: Introductionmentioning
confidence: 99%
“…The weakly hydrogen-bonded H 3 C-HF complex has been detected in the reaction of methane with F 2 in low-temperature noble gases using spectroscopic methods [13][14][15]. The structures, frequency shifts, and interaction energies of H 3 C-HF, H 3 C-HCCH, H 3 C-HCN, H 3 C-HNC, and H 3 C-H 2 O complexes have been investigated using quantum chemical calculations [8,[16][17][18][19][20][21]. The results show that the methyl radical can participate in singleelectron hydrogen bonding, but the bonding is relatively weak.…”
Section: Introductionmentioning
confidence: 99%